Adsorbents and removal strategies of non-steroidal anti-inflammatory drugs from contaminated water bodies. Issue 3 (June 2019) - Mlunguza, Nomchenge Yamkelani; Ncube, Somandla; Nokwethemba Mahlambi, Precious; Chimuka, Luke; Madikizela, Lawrence Mzukisi
Highlights: NSAIDs are predominant water pollutants and their removal strategies are examined. Several adsorbents reported for NSAIDs removal from water are re-usable. Toxicity of some NSAIDs degradation products in aquatic environment is not known. Adsorbents with higher surface area resulted in greater adsorption capacities. Few plant species have the ability to remove selected NSAIDs from water. Abstract: In the past few decades, there has been a rapid growth in the number of published articles that have focused on the environmental monitoring of non-steroidal anti-inflammatory drugs (NSAIDs). This is due to their extensive usage for the treatment of various diseases such as arthritis, musculo-skeletal pain and other various acute pains, because of their availability over the counter without a medical prescription. NSAIDs consumption is followed by excretion through fecal matter and urine which increases their concentration in the aquatic environment. Review articles focusing on the occurrence, fate, and removal of pharmaceuticals in the water environment have been reported. This review focusses on adsorbents and various ways of NSAIDs reduction in the environment that include activated carbon, ligninolytic enzymes, graphene-based adsorbents, molecularly imprinted polymers, electrochemical methods, sonochemical processes and photocatalytic degradation. The applicability of each adsorbent in removing NSAIDs from environmental surface water are deliberated in this review. Generally, it is observed that many adsorbents and processes are yet to be investigated for removal of NSAIDs in the large scale such as wastewater treatment plants. Other remedial approaches such as constructed wetlands have shown great potential for elimination of NSAIDs in wastewater effluent and are also discussed in this review. Also, the attainments and challenges, as well as views for future studies, are outlined and discussed in the current review.